Social Theory, Power and Practice - Tew, J. author. aut Link
X, 233 p.
Keywords: Social Theory, Power and Practice explores key strands of contemporary social theory in developing an innovative framework for understanding the operation of power. This draws on structural theories of inequality and oppression and poststructural deconstructions of discourse, identity and emotion. These are used to examine the dynamics of social and personal change, and to inform the development of empowering practice within the human services with those who may experience distress, abuse or exclusion.